Utilizing spinal cord injury stratification during classification for allocation of para surfing sport classes - Butkus, M.; Ganesan, M.; Muthaiah, V. P. K.; Johnson, M. E. (Journal of Science and Medicine in Sport, 2023)
Objectives The purpose of this study was to determine which stratification (anatomical versus functional) forms a better construct for classification of para surfers with spinal cord injury; to assess the groupings of these para surfers; and to evaluate the strength of association between manual muscle testing and surfing performance.